Green infrastructure applied to urban drainage: A Case Study of the Municipality of São Paulo - Godoy, Jeane Aparecida Rombi de; Benini, Sandra Medina; Palmisano, Angelo (Technical and Scientific Journal Green Cities, 2024)
This study primarily aims to evaluate the effectiveness of green infrastructure in managing stormwater and reducing floods in the watersheds of São Paulo. The research is justified by the increasing unregulated urbanization, which has exacerbated environmental problems such as soil impermeability and rising flood incidents. Green infrastructure emerges as a promising approach to mitigate these issues, promoting environmental sustainability and quality of life in urban areas. The methodology involves analyzing three specific watersheds in São Paulo: Córrego Mandaqui, Córrego Cabuçu de Baixo, and Córrego Jacu. Through multiple case studies, the research assesses the characteristics of these watersheds and the green infrastructure interventions implemented, such as linear parks and bioretention systems. Data collection was conducted through exploratory research and qualitative analysis, allowing for triangulation of information and identification of patterns and conflicts. The results indicate that green infrastructure has significantly contributed to reducing flood impacts and improving environmental quality in the analyzed watersheds, although challenges related to implementation and management persist, requiring more adaptive and context-specific approaches.
Keywords: Green Infrastructure; Stormwater Management; Urban Sustainability